Implementasi Alat Fingerpint pada Kedisiplinan Pegawai Negeri Sipil - Anindia Afit Putri Yanuarta; Ahmad Suprastio; Ida Swasanti (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The advancement of technology is increasingly present in everyday life and provides positive impacts for humans, including in the government sector. The implementation of technologies such as fingerprint-based attendance has become a crucial strategy to improve the discipline and efficiency of civil servants (ASN). This system replaces manual methods with more accurate and real-time technology, making attendance tracking easier and reducing the risk of data manipulation. This research utilizes a descriptive qualitative method, with data collected through observation, interviews, and documentation. The findings of the study reveal that the use of fingerprint attendance contributes to improved discipline and work efficiency. However, some technical challenges, such as device malfunctions and difficulties in reading fingerprints, still exist. The primary advantages of this system are speed, accuracy, and data integration, which support employee performance evaluation. With technical improvements and feature additions, the fingerprint system can offer more significant benefits over time.